Cholesterol interaction motifs in G protein‐coupled receptors: Slippery hot spots?. (7th February 2020) - Sarkar, Parijat; Chattopadhyay, Amitabha
Abstract: G protein‐coupled receptors (GPCRs) are cell membrane associated signaling hubs that orchestrate a multitude of cellular functions upon binding to a diverse variety of extracellular ligands. Since GPCRs are integral membrane proteins with seven‐transmembrane domain architecture, their function, organization and dynamics are intimately regulated by membrane lipids, such as cholesterol. Cholesterol is an extensively studied lipids in terms of its effects on GPCR structure and function. One of the possible mechanisms underlying modulation of GPCR function by cholesterol is via specific interaction of GPCRs with membrane cholesterol. These interactions of GPCRs with membrane cholesterol are often attributed to structural features of GPCRs that could facilitate their preferential association with cholesterol. In this backdrop, cholesterol interaction motifs represent putative interaction sites on GPCRs that could facilitate cholesterol‐sensitive function of these receptors. In this review, we provide an overview of cholesterol interaction motifs found in GPCRs, which have been identified through a combination of crystallography, bioinformatics analysis, and functional studies. In addition, we will highlight, using specific examples, why mere presence of a cholesterol interaction motif at a given site may not directly implicate its role in interaction with membrane cholesterol. We therefore believe that experimental approaches, followed by functional analysis of cholesterol sensitivity of GPCRs, would provide a better understanding of the role played by these motifs in cholesterol‐sensitive function. We envision that a comprehensive knowledge of cholesterol interaction sites in GPCRs would allow us to develop a better understanding of GPCR structure‐function paradigm, and could be useful in future therapeutics. This article is categorized under: Models of Systems Properties and Processes > Mechanistic Models Analytical and Computational Methods > Computational Methods Laboratory Methods and Technologies > Macromolecular Interactions, Methods Abstract : Cholesterol binding/interaction motifs in GPCRs.